Implications Of The Inquiry Strategy on Science Process Skills and Students Learning Outcomes in Learning Growth and Development Systems of Plants at SMA and MA Negeri Kembang Tanjong Pidie Regency - Muhammad Hafidillah; Hasanuddin Hasanuddin; Ali Sarong (Budapest International Research and Critics University, 2020)
This study aimed to determined the differences between learning with free inquiry strategies on science process skills and learning outcomes on the materials of growth and development at SMA and MA in Kembang Tanjong, Pidie Regency. Data was collected on 6 October to 10 November 2018. This study use a quantitative descriptive approach with a quasi-experimental research technique. The design in this study is a non-equivalent control group design. The collecting of data divided into two groups: the experimental group and the control group. The number of samples in this study were 50 students for the experimental class and 52 students for the control class. Hypothesis this study testing based on the SPSS program version 23.0 for windows of a significance level of 0.05 obtained results; the value of science process skills students 6,055> 1.98 (thitung> ttabel), the value of student learning outcomes of a significance level of 0.05 obtained sig value is 5.965> 1.98 (thitung> ttabel). Based on two variables measured show that the implementation of the inquiry strategy there are differences between the science process skills and student learning outcomes in the material growth and development in plants at SMA and MA Negeri KembangTanjong, Pidie Regency.